1987
DOI: 10.1039/c39870000570
|View full text |Cite
|
Sign up to set email alerts
|

2-Dimethylaminomethyl-3-trimethylsilylmethylbuta-1,3-diene as a synthetic equivalent of 2,2′-biallyl zwitterionic species

Abstract: The title compound reacts with nucleophiles followed by electrophiles in tandem or in the reverse order smoothly to give 1,2-dimethylenecyclohexanes and their oxa analogues; thus this reagent acts as the synthetic equivalent of 2,2'-biallyl zwitterionic species.We have previously reported that 2-dimethylaminomethyl-3-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In fact, study of the “activated” C–N bond has been conducted for many years. A quaternary ammonium salt is one of the most common N -containing substrates in organic synthesis. In 1998, Wenkert et al reported the first Ni-catalyzed Kumada-Corriu cross-coupling of aryltrimethylammonium iodides 347 with aryl and alkyl Grignard reagents . The feasibility of the C–N bond cleavage via oxidative addition of a Ni(0) species into a C–N bond of aryltrimethylammonium salts was demonstrated in this pioneering work. , Then Reeves et al reported the room temperature Pd-catalyzed cross-coupling of aryltrimethylammonium triflates 348 with aryl Grignard reagents yielding biaryls .…”
Section: Cleavage Of Activated C–n Single Bondsmentioning
confidence: 99%
“…In fact, study of the “activated” C–N bond has been conducted for many years. A quaternary ammonium salt is one of the most common N -containing substrates in organic synthesis. In 1998, Wenkert et al reported the first Ni-catalyzed Kumada-Corriu cross-coupling of aryltrimethylammonium iodides 347 with aryl and alkyl Grignard reagents . The feasibility of the C–N bond cleavage via oxidative addition of a Ni(0) species into a C–N bond of aryltrimethylammonium salts was demonstrated in this pioneering work. , Then Reeves et al reported the room temperature Pd-catalyzed cross-coupling of aryltrimethylammonium triflates 348 with aryl Grignard reagents yielding biaryls .…”
Section: Cleavage Of Activated C–n Single Bondsmentioning
confidence: 99%
“…23 Reaction of 54 with N-phenylmaleimide leads to the formation of the bis- The same authors demonstrated that this methodology could be applied to the stereoselective synthesis of tetracene derivatives, with potential application to the synthesis of tetracyclines. This methodology has been extended by both Trost 24 and Hosomi, 25 who have separately reported the utility of 58 and 59 as differentiated bifunctional reagents that are useful in heterolytic annulation reactions as well as tandem Diels-Alder cycloadditions.…”
Section: Equivalents Of 3-methylene-14-pentadiene and Related Species...mentioning
confidence: 99%
“…Transition-metal complexes can catalyze not only the addition of amines to dienes, but the cleavage of allylic amines as well. Studies that have been published or patented have uncovered catalysts for the deamination of allylic amines to generate dienes. Moreover, catalysts have been identified for the insertion of carbon monoxide into the C−N bond of allylic amines to form N -allyl amides . This process certainly involves a metal-mediated C−N bond cleavage at some part of the catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%